PENGARUH KOMITMEN PIMPINAN DAN LINGKUNGAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN (Survei Pada SKPD Provinsi Sulawesi Tengah) - Fitriani, Asri (Katalogis, 2017)
The research intends to describe the leaders’commitment, internal control environment, and the quality of financial statement; analyze the simultaneous influence of leaders ‘ commitment and internal control environment on financinal statement;determine and analyze the partial influence of internal control environment on financinal statement in all regional government working units in central Sulawesi. The research applies verificative approach. Population includes all regional government working units in central Sulawesi. Data used is primary and secondary data based on questionnaire distributed to 43 leaders in government working units who selected by census method. The result concludes that leaders ‘ commitment and internal control environment partially has significant influence on financial statement quality; internal control environment partially significant influence on financinal statement quality in all government working units in central Sulawesi.